(untitled) (Psicologia USP, 2008)
We have analyzed the results of an inquiry about mystic-religious cure practices (within both Protestant and Renovated Catholic Churches, as well as Umbanda afro-american spiritualism). Along with the comparison between those results and treatment, in Mental Health public nurseries, of individuals complaining from mental discomfort.. The statistic analysis revealed mystic-religious cure practices are efficacious at the solution of problems from those who recurred to these practices, overcoming, in the short term, the efficacy obtained by the nurserial practices. One of the main means for the mystic-religious cure practices efficacity consists in the meaning-providing from various hues, featuring the radical, imaginary-essence meaning, generating, in many cases, the institutional or ritualistic, fanactic kind conversion. Mystic-religious cure practices seem to function like contemporary individualism "illnesses" orthopedia, restoring, with sintony to the symptoms, some individual category's functionality. As the survey unfolds, we came to the hypothesis about the existence of a "Mysticism Culture", in advanced stage of formation within the Brazilian context, as a consequence of cultural features, as well as of the effects from subjective relation disturbances towards the symbolic field, inside globalized consummation societies with sharp social excludance rates and affected by an important meaning crisis following the weakening of the most basic ideals of liberalism.